2012
DOI: 10.1186/1472-6882-12-201
|View full text |Cite
|
Sign up to set email alerts
|

Epigallocathechin gallate, polyphenol present in green tea, inhibits stem-like characteristics and epithelial-mesenchymal transition in nasopharyngeal cancer cell lines

Abstract: BackgroundPrevious studies have demonstrated that the consumption of green tea inhibits the growth of various cancers. Most cancers are believed to be initiated from and maintained by a small population of cancer stem-like cells (CSC) or tumor-initiating cells (TIC) that are responsible for tumor relapse and chemotherapeutic resistance. Although epigallocathechin gallate (EGCG), the most abundant catechin in green tea, has been reported to induce growth inhibition and apoptosis in some cancer cells, its effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(48 citation statements)
references
References 45 publications
1
42
0
3
Order By: Relevance
“…Therefore, we focused on evaluating the mechanisms underlying the anti-invasive effects of pterostilbene at concentrations no greater than 10 μM. Recent studies have identified many diet-derived, natural products as inhibitors of EMT, including garlic-derived chemicals [20], the soy constituent genistein and green tea polyphenols [21]. In our study, we found that, after treatment with low-dose pterostilbene (10 μM) for 24 h, MDA-MB-231 cells displayed morphological alterations from the mesenchymal phenotype to the epithelial phenotype and possessed an epithelial-like morphology.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we focused on evaluating the mechanisms underlying the anti-invasive effects of pterostilbene at concentrations no greater than 10 μM. Recent studies have identified many diet-derived, natural products as inhibitors of EMT, including garlic-derived chemicals [20], the soy constituent genistein and green tea polyphenols [21]. In our study, we found that, after treatment with low-dose pterostilbene (10 μM) for 24 h, MDA-MB-231 cells displayed morphological alterations from the mesenchymal phenotype to the epithelial phenotype and possessed an epithelial-like morphology.…”
Section: Discussionmentioning
confidence: 99%
“…К настоящему моменту всесторонне изучена и подробно описана мультитаргетная противоопухолевая активность I3C, DIM и EGCG в отношении опухолей различного происхождения [17][18][19], в том числе и РЯ [20][21][22], а так-же обнаружена способность DIM [23,24] и EGCG [25,26] …”
Section: ингибиторы овариальных опухолевых стволовых клетокunclassified
“…Недавно было показано, что антиинвазивные и анти-метастатические свойства DIM in vitro и in vivo обуслов-лены подавлением экспрессии ключевых сигнальных бел-ков, опосредующих процесс эпителиально-мезенхималь-ного перехода (ЕМТ) опухолевых клеток [25]. Известно, что в результате обратимого процесса ЕМТ ОСК, вместе с измененной морфологией, вследствие перепрограмми-рования генотипа приобретают инвазивные свойства и метастатическую активность.…”
Section: рис 5 достоверные кластеры белков и цитокинов дифференциаunclassified
See 1 more Smart Citation
“…[137] EGCG inhibits the self-renewing capacity of human prostate cancer cell lines (PC-3 and LNCaP) containing a small population of CSCs presenting CD44 + CD133 + . Furthermore, EGCG also inhibits the self-renewing capacity of CD44 + α2β1+CD133 + CSCs isolated from human primary prostate tumors, as measured by spheroid formation in suspension.…”
Section: Future and Novel Targets For Tchmmentioning
confidence: 99%